2023
DOI: 10.1007/s12094-023-03112-w
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the diagnosis, treatment and prognosis of cancer: the rationale for an individualised approach

Abstract: Background Precision medicine in oncology aims to identify the most beneficial interventions based on a patient’s individual features and disease. However, disparities exist when providing cancer care to patients based on an individual’s sex. Objective To discuss how sex differences impact the epidemiology, pathophysiology, clinical manifestations, disease progression, and response to treatment, with a focus on data from Spain. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…Interestingly, absence of an association between male married status and TMT also highlights the importance of strati ed analyses according to sex. Indeed, married status is well known to exert a differential effect according to sex in a number of settings within multiple primaries [8,24]. For example, Rosiello et al showed that unmarried males have worse cancerspeci c mortality in metastatic renal cell carcinoma, while unmarried females do not [8].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, absence of an association between male married status and TMT also highlights the importance of strati ed analyses according to sex. Indeed, married status is well known to exert a differential effect according to sex in a number of settings within multiple primaries [8,24]. For example, Rosiello et al showed that unmarried males have worse cancerspeci c mortality in metastatic renal cell carcinoma, while unmarried females do not [8].…”
Section: Discussionmentioning
confidence: 99%
“…Gender differences in cancer incidence and mortality may be the result of a complex interaction between environmental and genetic factors. Moreover, socioeconomic inequalities can affect cancer occurrence differently in men and women, by involving unhealthy lifestyle behaviors, smoking habits, alcohol consumption, awareness of risks, occupational exposure, and access to healthcare [ 19 ]. Overall, the probability of developing cancer is greater in men than in women [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…As illustrated in Figure 1 , the incidence of specific cancers varies between males and females. Such disparities are often attributed to the influence of sex hormones ( 13 ). The nuanced interplay between sex hormones and cellular pathways in different tissues can either augment or suppress cancer's onset, progression, and response to therapies ( 14 ).…”
Section: Introductionmentioning
confidence: 99%